Clematis guniuensis (Ranunculaceae) is synonymous with C. baominiana, a morphologically distinctive species in China - Ye, Xi-Yang; Liu, Zhi-Gao; Xiong, Si-Min; Huang, Qiao-Lan; Su, Chun-Lan; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2025)
Based on consultation of literature and observations of both herbarium specimens (including type material) and living plants in the wild, we demonstrate that Clematis guniuensis, which was first described from Anhui province and then found to occur also in Zhejiang province, China, is not essentially different from C. baominiana, a morphologically distinctive species described from Hunan under the name C. villosa. We therefore place C. guniuensis in synonymy with C. baominiana herein.